Global evidence on falls and subsequent social isolation in older adults: a scoping review. Issue 9 (29th September 2022) - Thomas, Sonia M; Parker, Amanda; Fortune, Jennifer; Mitchell, Gary; Hezam, Areej; Jiang, Ying; de Groh, Margaret; Anderson, Kerry; Gauthier-Beaupré, Amélie; Barker, Joan; Watt, Jennifer; Straus, Sharon E; et al.
Abstract : Background: Falls are a leading cause of injury-related hospitalizations among adults aged 65 years and older and may result in social isolation. Objective: To summarise evidence on falls and subsequent social isolation and/or loneliness in older adults through a scoping review. Eligibility criteria: Studies were eligible for inclusion if the population had a mean age of 60 years or older, they examined falls and subsequent social isolation, loneliness, fear of falling or risk factors and were primary studies (eg, experimental, quasi-experimental, observational and qualitative). Sources of evidence: MEDLINE, CINAHL, Embase, Ageline and grey literature from inception until 11 January 2021. Charting methods: A screening and charting form was developed and pilot-tested. Subsequently, two reviewers screened citations and full-text articles, and charted the evidence. Results: After screening 4993 citations and 304 full-text articles, 39 studies were included in this review. Participants had a history of falling (range: 11% to 100%). Most studies were conducted in Europe (44%) and North America (33%) and were of the cross-sectional study design (66.7%), in the community (79%). Studies utilised 15 different scales. Six studies examined risk factors for social isolation and activity restriction associated with fear of falling. Six studies reported mental health outcomes related to falls and subsequent social isolation. Conclusions: Consistency in outcome measurement is recommended, as multiple outcomes were used across the included studies. Further research is warranted in this area, given the ageing population and the importance of falls and social isolation to the health of older adults. Scoping review registration number: 10.17605/OSF.IO/2R8HM.